Cardiac dimensions, intraventricular septum thickness in relation to the estimated glucose disposal rate individuals with long-standing type 1 diabetes: a cross-sectional analysis of the PARADISE T1DM study - Kulecki, Michał; Naskręt, Dariusz; Kamiński, Mikołaj; Kasprzak, Dominika; Lachowski, Paweł; Kulczycka, Ania; Kozłowska, Maria; Klause, Daria; Flotyńska, Justyna; Zozulińska-Ziółkiewicz, Dorota; Uruska, Aleksandra (Journal of Medical Science, 2024)
Aim. Insulin can stimulate the growth of various cells, including cardiomyocytes, through the insulin-like growth factor (IGF) signaling pathway. Insulin resistance (IR), characterized by elevated circulating insulin levels, complicates long-standing type 1 diabetes mellitus (T1DM). This study investigates whether IR in T1DM is associated with cardiac remodeling.Material and methods. IR was assessed using the estimated glucose disposal rate (eGDR) in 84 adults with T1DM of at least 5 years. Participants with an eGDR at or below the median value were considered more insulin resistant. Transthoracic echocardiography was used to measure left ventricular end-diastolic diameter (LVEDD), intraventricular septal thickness (IVST), right ventricular end-diastolic diameter (RVEDD), and left atrial diameter (LAD). Participants were divided into two groups based on the median eGDR value. Comparisons between groups were made using the Mann-Whitney test.Results. The median age of the participants was 40.5 years (range: 34.0-51.0), with a T1DM duration of 21.0 years (range: 15.5-27.0) and eGDR of 7.4 (range: 5.1-9.5). Of the participants, 52 (61.9%) were men. Individuals with lower eGDR had larger cardiac diameters (all in cm): LVEDD (4.5 [4.3-4.8] vs 4.75 [4.5-5]; p=0.01), LVEDD(2.7 [2.5-2.8] vs 2.8 [2.6-2.9]; p=0.02), end-systolic LAD (3.5 [3.2-3.7] vs 3.8 [3.5-3.9]; p